Формування професійно орієнтованої іншомовної комунікативної компетентності у студентів нелінгвістичних спеціальностей (Національний університет харчових технологій: із досвіду розробки) - Окопна, Яна Володимирівна (НПУ імені М.П.Драгоманова, 2014, 2014)
Статтю присвячено проблемі підготовки майбутніх фахівців сфери обслуговування. У роботі подаються основні вимоги до фахівців сфери туризму та особливості туристської освіти у вищих навчальних закладах. Визначено сутність і зміст компонентів готовності до професійної діяльності майбутніх фахівців та охарактеризовано критерії, показники і рівні їх прояву. Запропоновано модель підготовки студентів факультету туризму до професійної діяльності, психолого-педагогічні умови її іншомовної реалізації. The article is devoted to the problem of future specialists training in tourism. The basic requirements for the specialists in tourism sphere and peculiarities of tourist foreign language education in high schools are given in this work. The essence and contents of components readiness for future specialists’ professional activity in international tourism are determined and criteria, indexes and levels of their display are characterized. The model of the students training system of tourism faculty for sport health activity, psychological and pedagogical conditions of its foreign language realization, and also program and methods of the formation of future specialists’ readiness to the professional activity in sport-health tourism are offered. The basic results of scientific work have confirmed the effectiveness of the offered model of readiness formation to the future specialists’ foreign language professional activity in sport-health tourism in high schools. Also in the articles are listed components of professional training specialists on tourism issues and shows the main areas on which the teaching tourism specialists happening − managers of tourism and recreation, financial managers, animators, guides, experts in cultural tourism. The article examines the current state and realities of the processes of preparation specialists of the tourism industry in Ukraine. Tourism industry declared as a priority sector of the national economy in Ukraine. That is why tourism needs availability of qualified and competent personnel who have continued to develop the tourism industry at a high level. The article identifies the key requirements for professional skills of future professionals.
Keywords: фахова діяльність; програма підготовки; формування готовності до професійної діяльності; professional activities; training; formation of readiness for professional activities; кафедра іноземних мов професійного спрямування